Country Partnership Framework for Azerbaijan for the Period FY16-FY20 - World Bank Group (World Bank, Washington, DC, 2015)
The country partnership framework (CPF) for Azerbaijan covering the period FY2016-20, sets out the World Bank Group (WBG) support to the country on its path toward a sustainable, inclusive, and private sector-led growth underpinned by a diversified asset base. The country’s strategic goals are laid out in its development strategy - Azerbaijan 2020: vision for the future and other strategic documents that aim at reducing Azerbaijan’s dependence on oil and gas revenues and strengthening its resilience to external shocks through investments into diversified human capital, physical infrastructure, and stronger institutions. The CPF builds on the WBG systematic country diagnostic (SCD) for Azerbaijan and aligns its objectives with the constraints and priorities identified in the SCD. Over the past decade, Azerbaijan has made remarkable progress toward reducing poverty and boosting shared prosperity. In response to the emerging challenges and the mounting depreciation pressures, the government devalued the national currency and committed to fiscal consolidation. The CPF takes into account the government’s intention to optimize the external borrowing over the medium term as part of the ongoing effort to maintain fiscal sustainability. The CPF lending program will help Azerbaijan in meeting its development objectives through engagement in priority areas where the country’s ownership is strong, where the WBG has a comparative advantage and where the potential impact on the WBG twin goals is substantial. The CPF will address the SCD connectivity agenda through investments into the development of the county’s transport and transit corridors as well as improvement of local infrastructure at the community level. The CPF results are grouped around two focus areas and eight objectives that aim at improved public sector management and service delivery, and enhanced economic competitiveness.